The Antimicrobial Potential of the Neem Tree Azadirachta indica - Wylie, Marina R.; Merrell, D. Scott (Frontiers in Pharmacology, 2022)
Azadirachta indica (A. Juss), also known as the neem tree, has been used for millennia as a traditional remedy for a multitude of human ailments. Also recognized around the world as a broad-spectrum pesticide and fertilizer, neem has applications in agriculture and beyond. Currently, the extensive antimicrobial activities of A. indica are being explored through research in the fields of dentistry, food safety, bacteriology, mycology, virology, and parasitology. Herein, the most recent studies that demonstrate the potential of neem as a previously untapped source of novel therapeutics are summarized as they relate to the aforementioned research topics. Additionally, the capacity of neem extracts and compounds to act against drug-resistant and biofilm-forming organisms, both of which represent large groups of pathogens for which there are limited treatment options, are highlighted. Updated information on the phytochemistry and safety of neem-derived products are discussed as well. Although there is a growing body of evidence that supports the use of A. indica as an antimicrobial, additional studies are clearly needed to determine the specific mechanisms of action, clinical efficacy, and in vivo safety of neem as a treatment for human pathogens of interest. Moreover, the various ongoing studies and the diverse properties of neem discussed herein may serve as a guide for the discovery of new antimicrobials that may exist in other herbal panaceas across the globe.